Developing culture-based materials with integrated performance assessment - Dewi, Ridha Ayu Karisma; Wiedarti, Pangesti (Department of Applied Linguistics, FBSB, Universitas Negeri Yogyakarta, 2020)
The aims of this study were to identify the target needs, describe the learning needs and describe the appropriate culture-based material with Integrated Performance Assessment for the eighth grade students of SMP N 1 Muntilan. This study was classified as research and development (R&D). The study procedure was adapted from ADDIE models proposed by Branch (2009). The data were collected through questionnaires (need analysis questionnaire, expert judgment rating scale, interview transcripts, and questionnaire for students about the materials). The data from the needs analysis, the expert judgment questionnaire, and the questionnaire for students about the materials were analyzed quantitatively using frequency and percentage. Meanwhile, the data from the interview were analyzed using descriptive. The materials in the developed materials were developed based on Curriculum 2013. The research findings showed that the developed materials was considered appropriate. The result of the materials evaluation questionnaire was 3.81 which categorized as very good.